The Effect of Smartphone Technology Development on Student Morality - Didin Komarudin; Adnan Adnan; Asrizal A. Upe (UIN Sunan Gunung Djati Bandung, 2017)
This research is formulated: How is the effect of technological development on student morality? What are the positive and negative impacts of technological development for students? What can strengthen student solidarity? The purpose of this study is to determine the effect of technological development on student morality. Know the positive and negative impact of technological advances. Know the things that can strengthen student solidarity. Case study method with qualitative analysis. Researchers conducted direct interviews on students, studying moral books, internet, research-related research researchers, and so forth.